The value of echocardiography in the staging of preexcitation syndrome and the assessment of left ventricular wall dyskinesia in children - Yuan, Yahui; Li, Shu; Chen, Jun; Mao, Yu; Yang, Ming; Yang, Shiwei; Kong, Wentao; Liu, Hao (Frontiers in Pediatrics, 2025)
BackgroundThe incidence of Wolff-Parkinson-White syndrome (WPWs) in the pediatric population is increasing recently. Conventional echocardiography lacks specificity and was limited to assessing the effects of WPWs on cardiac structure, while changes in cardiac function, ventricular wall dysfunction and different subtypes of WPWs were less commonly addressed. Whether WPWs causes cardiac decompensation and ventricular dyskinesia was controversial. Whether echocardiographic multiparameter indices can improve the diagnostic specificity and guide the classification of WPWs and assess the recovery of left ventricular (LV) synchrony and ventricular wall dyskinesia in patients after radiofrequency ablation (RFA) is a very important direction of research.ObjectivesTo analyse the echocardiographic performance of patients with WPWs: (1) to assess the hazard of WPWs on cardiac function and LV wall dyskinesia using ultrasound multiparameters, with the aim of exploring in depth the pattern of effect of WPWs on cardiac function and motion, (2) to attempt to use echocardiography for staging WPWs, and (3) to predict patient recovery after RFA.MethodsThe clinical, echocardiographic and RFA data of 75 children with RFA-confirmed WPWs from January 2019 to December 2024 were retrospectively analysed and compared with 60 healthy controls during the same period. All statistical analyses were carried out using SPSS 26.0 and P-values <0.05 were considered statistically significant.ResultsTwo-dimensional echocardiography demonstrated significant LV enlargement, reduced LV systolic function, and significant ventricular wall dyskinesia in 14 of 75 patients, basal segmental septal dyskinesia in 5, and LV posterior wall dyskinesia in 4. The remaining 52 patients did not have significant ventricular wall dyskinesia. Multiparameters showed that WPWs patients compared with healthy controls: GLS (−18.16 ± 3.54% vs. −22.88 ± 0.71%), TDSD (38.88 ± 6.77 ms vs. 24.03 ± 1.90 ms), TDRV−LV (41.18 ± 7.21 ms vs. 24.32 ± 1.94 ms), PSD (35.26 ± 5.42 ms vs. 22.44 ± 2.23 ms), and MPTD (196.92 ± 61.41 ms vs. 100.55 ± 10.25 ms) were all statistically different from each other (P < 0.05). LVEDD Z score (1.07 ± 0.84 vs. 1.05 ± 0.56), LVEF (61.20 ± 9.02% vs. 66.52 ± 3.16%) was not significantly different between the two groups (P > 0.05). Seventy-five patients underwent RFA among them, 28 cases of type A bypass and 47 cases of type B bypass, analysed the longitudinal strain bull's-eye diagram of the LV, it was concluded that the GLS of the inferior, inferior lateral and anterior lateral walls of type A bypass was significantly reduced, and the GLS of the anterior wall, anterior septum and inferior septum of type B bypass was significantly reduced, with the most significant in the basal segment, followed by the intermediate segment, and the apical region was not involved. All the postoperative ultrasound parameters were better than the preoperative ones, and the results of the 3-month postoperative review showed that there was a difference between the ventricular synchronisation indexes and those of the healthy group, suggesting that the LV synchronisation had not yet completely returned to normal. ROC curve analysis showed GLS, TDSD, TDRV−LV, PSD and MPTD could predict the prognosis of recovering post RFA.ConclusionsConventional echocardiography and two-dimensional speckle tracking imaging have the capacity to provide reference data for the reduction of cardiac function and ventricular wall motion disorder caused by WPWs. Furthermore, the longitudinal strain bull's eye map of two-dimensional speckle tracking imaging has the potential to guide the classification of WPWs. Furthermore, a multitude of echocardiographic parameters have been shown to predict the prognosis of recovering post RFA.